2021
DOI: 10.1371/journal.pone.0250203
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation of pear flowers with Metschnikowia reukaufii and Acinetobacter nectaris enhances attraction of honeybees and hoverflies, but does not increase fruit and seed set

Abstract: Currently, one of the most important challenges is to provide sufficient and affordable food and energy for a fast-growing world population, alongside preserving natural habitats and maintaining biodiversity. About 35% of the global food production depends on animals for pollination. In recent years, an alarming worldwide decline in pollinators has been reported, putting our food production under additional pressure. Therefore, there is an urgent need to find sustainable ways to ensure this crucial ecosystem s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 62 publications
1
21
1
Order By: Relevance
“…Despite this, no effect on fruit set was observed in two consecutive years of treatment. The authors hypothesized however that this lack of an effect was likely due to the hosts not being pollen-limited, and further, that under such conditions, treating flowers with attractive microbes could potentially boost pollination . In another study involving almond, Schaeffer et al also observed a neutral effect of nectar-inhabiting microbes on pollination, as measured through pollen tube number.…”
Section: Potential Effects Of Floral Microbes On Beneficial Insectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, no effect on fruit set was observed in two consecutive years of treatment. The authors hypothesized however that this lack of an effect was likely due to the hosts not being pollen-limited, and further, that under such conditions, treating flowers with attractive microbes could potentially boost pollination . In another study involving almond, Schaeffer et al also observed a neutral effect of nectar-inhabiting microbes on pollination, as measured through pollen tube number.…”
Section: Potential Effects Of Floral Microbes On Beneficial Insectsmentioning
confidence: 99%
“…Recent work in wildflower systems has revealed that floral microbes can affect plant reproductive outcomes; however, evidence for such an effect in agricultural systems is limited. In a recent study conducted with pear, Colda et al found that application of a mixture of M. reukaufii and Acinetobacter nectaris at bloom can increase hoverfly and honey bee visitation to blossoms. Despite this, no effect on fruit set was observed in two consecutive years of treatment.…”
Section: Potential Effects Of Floral Microbes On Beneficial Insectsmentioning
confidence: 99%
“…However, to our knowledge, little work has been done to address the influence of nectar microbes on non-bee flower visitors. Two studies on Dipteran species have revealed an attraction to nectar yeasts and bacteria: hoverflies and mosquitoes ( Culex pipiens ) are attracted to the bacterium Acinetobacter nectaris and nectar yeasts M. reukaufii and Lachancea thermotolerans , respectively [94,133]. Nectar sugars were not addressed in either of these studies though, with VOCs instead noted to play an important role in attraction.…”
Section: Current Research and Future Directions On Nectar Microbe Eff...mentioning
confidence: 99%
“…This possibility suggests potential for both additive and non-additive effects of nectar microbe assemblages on nectar chemistry and pollinator health. Indeed, recent studies have revealed that yeast and bacteria consortia can increase nectar scent in an additive manner and can have positive effects on honeybee and hoverfly visitation [44,94], yet effects on bumblebee reproduction and colony development are no better than exposure to individual species alone [88]. Considerable work remains, however, as to the effect of nectar microbe consortia on pollinator attraction, nectar feeding, and health [95].…”
Section: (C) Effects Of Microbe-microbe Interactions In Nectar On Pol...mentioning
confidence: 99%
“…However, it was demonstrated that pear flowers are not as attractive as the flowers of other crops, such as apple, peach, and rape, due to the low volume and sugar concentration of their nectar [13,14,17]. Microorganism inoculation, bee attractants, pollen trapping, and syrup feeding have been explored to promote honey bee foraging and pear pollination in orchards [18][19][20].…”
Section: Introductionmentioning
confidence: 99%